Scientific Research as a Mechanism of Effective Human Development - (:unkn) unknown (Sofia, Bulgaria, International Scientific Unity, 2024)
The collection of abstracts presents the materials of the participants of the International scientific and practical conference «Scientific Research as a Mechanism of Effective Human Development». The collection of theses contains relevant research that can be useful for scientists, teachers, students and everyone who is interested in the development of science and expanding their knowledge in various fields. The materials of the collection are presented in the author's edition and printed in the original language. The authors of the published materials bear full responsibility for the authenticity of the given facts, proper names, geographical names, quotations, economic and statistical data, industry terminology, and other information.